KEBIJAKAN KRIMINAL TERHADAP PENCEGAHAN PENCURIAN KENDERAAN BERMOTOR (STUDI DI KEPOLISIAN SEKTOR SUNGGAL) - Eko Hartanto; Madiasa Ablisar; Mahmud Mulyadi; Marlina Marlina (USU LAW JOURNAL, 2015)
ABSTRACT Motor vehicle theft problem in the community is no longer a new thing, because almost every day many cases moto vehicle theft. Location of motor vehicle thefts occur in many places, but generally the same modus operandi. Nowadays, these criminal motor vehicle theft, especially theft is increasing, because the sanction given to the offender the theft of a motor vehicle is considered less severe, so many actors are already free repeat such action. This research is important to know why the highest motor vehicle theft happened in the jurisdiction of Police Sunggal. Furthermore, the data also showed, Crime Settlement (PTP) in Sunggal Police also did not show significant numbers.